2012
DOI: 10.1111/j.1756-185x.2012.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathies presenting as inflammatory arthritis: uncommon but important – a case series

Abstract: Occurrence of inflammatory arthritis with plasma dyscrasias is more than a chance association. Plasma cell dyscrasias should be ruled out in any elderly patient presenting with atypical arthritis with disproportionately high ESR, high creatinine and hyperglobulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Based on these findings, early detection of MG through regular laboratory work in patients with immune‐related conditions as underlying disease is important in establishing a treatment plan that can monitor progression from MGUS to MM and prevent end organ disease damage. A recent study showed that evaluation of plasma cell dyscrasia should be performed for any elderly patient with atypical arthritis and high disease activity . Therefore, we also suggest that MG should be ruled out for elderly patients with prolonged autoimmune diseases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on these findings, early detection of MG through regular laboratory work in patients with immune‐related conditions as underlying disease is important in establishing a treatment plan that can monitor progression from MGUS to MM and prevent end organ disease damage. A recent study showed that evaluation of plasma cell dyscrasia should be performed for any elderly patient with atypical arthritis and high disease activity . Therefore, we also suggest that MG should be ruled out for elderly patients with prolonged autoimmune diseases.…”
Section: Discussionmentioning
confidence: 85%
“…For example, the occurrence of monoclonal immunoglobulin is frequent in chronic inflammatory disorders such as chronic infection and autoimmune disorders . In particular, several recent reports on the close relationship between monoclonal gammopathy (MG) and Sjögren syndrome (SS) or inflammatory arthritis suggested that the link between MG and systemic autoimmune diseases requires greater attention . However, the association between MG and immune‐related conditions has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, age greater than fifty years, bilateral eye involvement, and high ESR at presentation were suggestive of a diagnosis of AAION. However, a high ESR is a common laboratory finding in patients with serous monoclonal gammopathies [11], hence its specificity for the diagnosis of AAION may be scarce in these patients. CRP values, instead, were within the normal range in the present case, suggesting that CRP could be a more specific index of AAION in patients with coexisting plasma cell dyscrasias.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Srinivasulu et al reported a case series of 6 patients in 2012, 5 of which were seronegative for RF and anti-CCP antibodies and 1 was positive for both [ 6 ]. Two separate cases of MM presenting as inflammatory polyarthritis were reported by Fedric and Agarwal.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%